Implementasi Manajemen Berbasis Sekolah dalam Meningkatkan Budaya Mutu Sekolah di MTs Miftahul Huda Bekasi - Zakiyah Mawaddah; Yon AE; Luluh Abdillah Kurniawan (Indo Publishing, 2025)
This research is motivated by the importance of improving the quality of education through the implementation of School-Based Management (SBM), which provides autonomy, flexibility, and active participation of all school stakeholders. MTS Miftahul Huda Bekasi was selected as the research site because the school has applied SBM principles in its institutional management and has successfully demonstrated a number of academic and non-academic achievements. The aim of this study is to analyze the factors influencing the implementation of SBM, to describe strategies for managing school resources, and to evaluate its impact on strengthening the quality culture within the madrasa. The research method employed is qualitative with a descriptive approach. Data were collected through observation, in-depth interviews with the principal, teachers, students, and parents, as well as documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with validity tested through source, technique, and time triangulation. The findings indicate that SBM implementation at MTS Miftahul Huda is carried out by involving the active participation of the principal, teachers, staff, students, parents, and the school committee in planning, implementation, and program evaluation. The strategies employed include improving teacher competence through training, applying democratic leadership, strengthening communication with parents, and developing a life skills–based curriculum. The positive impacts of SBM implementation are evident in improved school discipline, increased student learning motivation, the growth of responsibility, and the creation of a conducive learning environment. This study concludes that consistent implementation of School-Based Management is able to strengthen the quality culture at MTS Miftahul Huda Bekasi. Therefore, SBM implementation is recommended to be further enhanced through teacher training support, optimization of the school committee’s role, and expansion of community partnerships.